Association of eating frequency with anthropometric indices and blood pressure in children and adolescents: the CASPIAN-IV Study - Roya Kelishadi; Mostafa Qorbani; Mohammad Esmaeil Motlagh; Ramin Heshmat; Gelayol Ardalan; Maryam Bahreynian (Elsevier, 2016)
Abstract Objectives: This study was conducted to explore the association of eating frequency (EF) with anthropometric indices and blood pressure (BP) in children and adolescents. Methods: This nationwide cross-sectional study was performed on a multi-stage sample of 14,880 students, aged 6-18 years, living in 30 provinces in Iran. Parents were asked to report dietary intake of children as frequency of food groups and/or items. EF was defined as the sum of the daily consumption frequency of main meals and snacks. Association of EF with weight disorders, abdominal obesity, and elevated BP was assessed using different logistic regression models adjusted for potential confounding factors. Results: Eating more frequently (≥6 vs. ≤3) was found among students who were at younger age (11.91 vs. 13.29 years) (p < 0.001). Students who reported an EF of 4 (OR: 0.67, CI: 0.57-0.79), 5 (OR: 0.74, CI: 0.62-0.87), and 6 (OR: 0.54, CI: 0.44-0.65) had lower odds of being obese compared to those who had EF ≤ 3. Having EF of 4 (OR: 0.82, CI: 0.71-0.94), 5 (OR: 0.86, CI: 0.74-0.99), and ≥6 (OR: 0.73, CI: 0.63-0.85) was related to lower prevalence of abdominal adiposity. Conclusion: Higher EF was associated with lower mean values of anthropometric and BP measures, as well as with lower prevalence of generalized and abdominal obesity in children and adolescents. Longitudinal studies are needed to assess the long-term effects of EF on body composition in the pediatric age group.